PENGUKURAN LINIERITAS TINGKAT KEABUAN (GRAY LEVEL) CITRA FLUOROSKOPI MENGGUNAKAN METODE PENGOLAHAN CITRA DIGITAL - Fitri Mahardika Sari; Suryono Suryono (Youngster Physics Journal, 2014)
Measurement on the grey level on a plane fluoroscopy has done using processing image digital methods. The research aims to create computer software that is used to calculate the value of the image of grey level to test linierity gray level image fluoroscopy. The research can be used to help improve the quality of medical services as well as help in establishing the diagnosis.The research is done with exposed the panthom leeds test object gray scale laid between an x-ray source and image intensifier. This exposed done with variation voltage tube between 40 kvp to 63 kvp. Phantom which exposed are generates an image in the form of DICOM, then transferred to analyzed gray level using a computer. On the stage analysis made a computer program by using matlab consisting of the subroutine is: load citra DICOM, then taking an area ROI in each step, in regions ROI grey value in the average level of the voltage lowest 40 kvp until with voltage kvp, 63 its average value at one voltage a tube made a graph linierity between grey level step, with the level of then determine the equation linieritas and value of the coefficients correlation.The results obtained in research shows all variation in voltage tube having tested linierity high with indicated value of a coefficient correlation approaching +1 panthom used against image. The lowest in voltage to the voltage tests indicating the highest level linierity good increasingly. In voltage lowest voltage tube 40 kvp obtained linear equations y= 3.078x-3.461 with a coefficient correlation 0,8624 and in voltage highest earned 64 kvp in a linear equation y= 5.480x+10.431 with a coefficient correlation 0,9968. These results also indicated that gray level as part of software based matlab can be used to know the value of an image linierityf luoroskopi.Keywords: gray level, digital images, fluoroscopy image, DICOM, linierity